2022
DOI: 10.3390/nano12152700
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Hexagonal Prism-like Defective BiOCL Hierarchitecture for Photocatalytic Degradation of Tetracycline Hydrochloride

Abstract: Oxygen vacancy manipulation and hierarchical morphology construction in oxygen-containing semiconductors have been demonstrated to be effective strategies for developing high efficiency photocatalysts. In most studies of bismuth-based photocatalysts, hierarchical morphology and crystal defects are achieved separately, so the catalysts are not able to benefit from both features. Herein, using boiling ethylene glycol as the treatment solution, we developed an etching-recrystallization method for the fabrication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Further, it has been reported that photocatalytic degradation can be improved by utilizing nanomaterials, nanocomposites, or nanostructures. Nanomaterials for photodegradation must feature an appropriate bandgap (~3 eV), controllable electron-hole recombination rates, electrical conductivity, and corrosion resistance [178][179][180]. In that regard, photodegradation assisted by semiconductor nanomaterials or nanocomposites is promising because of their charge separation and ability to effectively absorb light in the visible region.…”
Section: Nanomaterials For the Photodegradation Of Pollutantsmentioning
confidence: 99%
“…Further, it has been reported that photocatalytic degradation can be improved by utilizing nanomaterials, nanocomposites, or nanostructures. Nanomaterials for photodegradation must feature an appropriate bandgap (~3 eV), controllable electron-hole recombination rates, electrical conductivity, and corrosion resistance [178][179][180]. In that regard, photodegradation assisted by semiconductor nanomaterials or nanocomposites is promising because of their charge separation and ability to effectively absorb light in the visible region.…”
Section: Nanomaterials For the Photodegradation Of Pollutantsmentioning
confidence: 99%